PRE-SERVICE TEACHERS' CLASSROOM MANAGEMENT PRACTICES AND PERCEIVED SCIENCE PROCESS SKILLS IN MADRASAH IBTIDAIYAH - Juhji Juhji; Mansur Mansur; Falyad’u Nadiyah; Ira Marliana (PEDAGOGIK : JURNAL PENDIDIKAN, 2026)
Developing students' science process skills is a key goal of inquiry-based science education, but empirical research on how pre-service teachers' classroom management methods enhance these skills is scarce, particularly in Islamic primary education. This study investigated how pre-service teachers' classroom management strategies influenced their perceptions of students' science process skills. A quantitative cross-sectional approach was used, with 52 pre-service teachers enrolling in or having completed a teacher professional education program. A structured questionnaire was used to collect data on classroom management methods and students' perceived science process skills, which were then analyzed using descriptive statistics and simple linear regression. Classroom management practices positively impact students' science process skills (β = 0.715, t = 7.224, p < 0.001). Effective classroom management leads to higher perceptions of students' ability to plan investigations, conduct observations, analyze data, draw conclusions, and communicate findings. These findings contribute to the classroom management literature by emphasizing its pedagogical function in promoting inquiry-based science learning from the perspective of pre-service teachers. Practically, the study emphasizes the necessity of improving classroom management competences in teacher education programs to better prepare future teachers to enable science learning and increase students' science process skills.